Food acid content and erosive potential of sugar‐free confections. (19th April 2017) - Shen, P; Walker, GD; Yuan, Y; Reynolds, C; Stacey, MA; Reynolds, EC
Abstract: Background: Dental erosion is an increasingly prevalent problem associated with frequent consumption of acidic foods and beverages. The aim of this study was to measure the food acid content and the erosive potential of a variety of sugar‐free confections. Methods: Thirty sugar‐free confections were selected and extracts analysed to determine pH, titratable acidity, chemical composition and apparent degree of saturation with respect to apatite. The effect of the sugar‐free confections in artificial saliva on human enamel was determined in an in vitro dental erosion assay using change in surface microhardness. Results: The change in surface microhardness was used to categorize the confections as high, moderate or low erosive potential. Seventeen of the 30 sugar‐free confections were found to contain high concentrations of food acids, exhibit low pH and high titratable acidity and have high erosive potential. Significant correlations were found between the dental erosive potential (change in enamel surface microhardness) and pH and titratable acidity of the confections. Ten of these high erosive potential confections displayed dental messages on the packaging suggesting they were safe for teeth. Conclusions: Many sugar‐free confections, even some with 'Toothfriendly' messages on the product label, contain high contents of food acids and have erosive potential.